Relationship between cathepsins and cardiovascular diseases: a Mendelian randomized study - Li, Qiaoqiao; Zhou, Zhongzheng; Xu, Teng; Gao, Xueping; Lou, Yake; Chen, Zijun; Zhang, Muzi; Fang, Qinghua; Tan, Jie; Huang, Jing (Frontiers in Pharmacology, 2024)
Background: Cardiovascular diseases (CVDs) are the leading age-related disorders worldwide, with their prevalence increasing annually. Cathepsins are protein-degrading enzymes essential for processes such as intracellular protein breakdown, apoptosis, and immune responses. Recent studies suggest a potential link between cathepsins and CVDs, yet the exact causal relationship remains to be elucidated. To address this, we propose using Mendelian randomization (MR) to explore the causal relationships between cathepsins and CVDs.Our MR analysis reveals that cathepsin E is a risk factor for MI and IS, cathepsin L2 offers protective effects against CHF and AF, and cathepsin O increases the risk for IS and AF.